Estimating Carbon Sequestration of Green Roof Plants in Tropical Climate - Md. Yacob, Mohamad Norfekry; Kasmin, Hartini; Hashim, Muhammad Iqbal Hakeem (International Journal of Integrated Engineering, 2021)
A green roofs is one of the recommended methods of practice in improving the sustainability of urban areas. Green roofs can be used as a passive technique to reduce carbon dioxide (CO2) emissions from the atmosphere. This is due to the role of green roof layers which are vegetation and soil to process the photosynthesis activities and to capture CO2 from the atmosphere. The objective of this paper is to quantify and to compare the amount of CO2 sequestration by ten potential green roof plants, in order to estimate the CO2 reduction within the surrounding atmosphere. It is found that, by planting the Alternanthera Paronychioides (Alternanthera P.) on the roof surface could reduce the indoor air temperature as well as the CO2, thus enhance the quality of air. This study also revealed that the Alternanthera P. generates the highest photosynthesis rate or CO2 uptake compared to the other nine plants, as high as 23.59 Î¼mol CO2 m-2s-1. It is predicted that if the Alternanthera P. is to be installed on a 0.64 m2 test bed roof, the CO2 could be reduced almost 0.010 tonnes, annually. This suggested that by planting Alternanthera P. on the roof surfaces may potentially give advantages on mitigating the greenhouse gas emission, particularly CO2, and reducing the impact of global warming.